Blood pressure control among diabetic hypertensives under cardiology follow-up at a regional hospital in rural Malaysia - Mohd. Shah, Azarisman; Abdullah, Aszrin; Omar, Ahmad Marzuki; Nik Ahmad, Nik Nur Fatnoon; Abdullah, Hilmi; Hasmoni, Mohamed Hadzri; Ngow, Harris Abdullah; Shah, Anis; Rathor, Mohammad Yousuf; Ab Rahman, Jamalludin (Southeast Asian Ministers of Education Organization (SEAMEO), 2010)
Three hundred thirty-one consecutive patients presenting with hypertension to the outpatient medical clinic of Tengku Ampuan Afzan Hospital, Kuantan, Malaysia were screened and 150 patients with concurrent diabetes were enrolled into a cross-sectional study. The majority of patients were male (60.6%) with a mean age of 60.0 +/- 11.0 years. The mean systolic blood pressure (SBP) was 140.9 +/- 20.1 mmHg and the mean diastolic blood pressure (DBP) was 81.7 +/- 9.8 mmHg. Only 38.0% (57/150) of patients had blood pressures within recommended guidelines (130/80 mmHg). The mean blood pressure in this group was 123.7 +/- 8.5/76.4 +/- 5.6 mmHg. The majority of patients were on either 2 (41.3%) or 3 (31.3%) anti-hypertensives. Females had a significantly higher SBP 145.4 +/- 22.7 vs. 138.0 +/- 17.8 mmHg in males (p = 0.026). The level of blood pressure control in diabetics was unsatisfactory, especially in females and the elderly. A reassessment of priorities in the management of patients with concurrent hypertension and diabetes is therefore, urgently needed.